2018
DOI: 10.1016/j.jfoodeng.2018.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterisation of biodegradable PLA nanoparticles loaded with thymol to improve its antimicrobial effect

Abstract: Highlights-PLA nanoparticles loaded with Thymol were prepared for the first time.-The PLA was found to be the key variable in optimizing the nanoparticle preparation.-The nanoparticles exhibited a high storage stability over a wide range of pHs.-The antimicrobial activity of the nanoparticles was tested on apple pieces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 24 publications
2
12
0
1
Order By: Relevance
“…The EE% was determined considering only the three major components of EOt and it corresponded to 52.81 ± 2.69% (Table II) for o-cymene, γ -terpinene, and thymol. These results are consistent with those of Marcet et al [47], who obtained thymol-loaded PLA NC with a mean size next to 260 nm and an EE of 60.3 ± 8%. In addition, they demonstrated that thymol-loaded PLA NC had improved antimicrobial properties in comparison with the non-encapsulated thymol.…”
Section: B Physicochemical Characterization Of Nc-eotsupporting
confidence: 93%
“…The EE% was determined considering only the three major components of EOt and it corresponded to 52.81 ± 2.69% (Table II) for o-cymene, γ -terpinene, and thymol. These results are consistent with those of Marcet et al [47], who obtained thymol-loaded PLA NC with a mean size next to 260 nm and an EE of 60.3 ± 8%. In addition, they demonstrated that thymol-loaded PLA NC had improved antimicrobial properties in comparison with the non-encapsulated thymol.…”
Section: B Physicochemical Characterization Of Nc-eotsupporting
confidence: 93%
“…However, only 23% of bixin loss was observed in biscuit dough baked at 150°C for 30 min, showing that the matrix presents a considerable influence on the carotenoid stability. Many experiments about the encapsulation of carotenoids by polymers in the aim to enhance their thermal stability were already reported, and PLA is a widely used polymer in the field 31–33 . Our system might produce an effect similar to matrix encapsulation, where the bioactive compound is uniformly distributed over the formed biopolymer carrier system 34 .…”
Section: Resultsmentioning
confidence: 97%
“…Many experiments about the encapsulation of carotenoids by polymers in the aim to enhance their thermal stability were already reported, and PLA is a widely used polymer in the field. [31][32][33] Our system might produce an effect similar to matrix encapsulation, where the bioactive compound is uniformly distributed over the formed biopolymer carrier system. 34 PLA might offer a protection towards oxygen and heat.…”
Section: Thermal Stability Of Bixin During Film Processingmentioning
confidence: 99%
“…PLA has been widely used in biomedicine, and it is considered to be a good material for preparing micron and nanoparticles because the particle size and shape can be controlled to meet the preparation requirements [100]. Using PEG-PLA-PEG nanoparticles as a delivery carriers for oral immunization enhanced mucosal uptake results in an effective immune response that preserves the antigenicity of the encapsulated HBsAg [101].…”
Section: Poly(lactic Acid)mentioning
confidence: 99%